2020
DOI: 10.1101/2020.09.30.321224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An improved experimental pipeline for preparing circular ssDNA viruses for next-generation sequencing

Abstract: We present an optimized protocol for enhanced amplification and enrichment of viral DNA for Next Generation Sequencing of begomovirus genomes. The rapid ability of these viruses to evolve threatens many crops and underscores the importance of using next generation sequencing efficiently to detect and understand the diversity of these viruses. We combined enhanced rolling circle amplification (RCA) with EquiPhi29 polymerase and size selection to generate a cost-effective, short-read sequencing method. This opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Frozen leaf tissue was ground, total DNA was extracted using the MagMax Plant DNA Isolation Kit (Thermo Fisher Scientific, Waltham, MA, USA), and DNA <6 Kb in size was selected using the Blue Pippin Prep system (model no. BDQ3010, Sage Science, Beverly MA) prior to library prep [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frozen leaf tissue was ground, total DNA was extracted using the MagMax Plant DNA Isolation Kit (Thermo Fisher Scientific, Waltham, MA, USA), and DNA <6 Kb in size was selected using the Blue Pippin Prep system (model no. BDQ3010, Sage Science, Beverly MA) prior to library prep [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…This process was repeated six times with a total of seven rounds including the initial inoculated plant. Total DNA was isolated but was not size-fractionated because earlier serial experiments showed that sequencing total DNA samples produce sufficient read coverage for viral diversity analysis [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing libraries for Veg2 and Veg6 were generated using EquiPhi polymerase (Thermo Fisher Scientific, Waltham MA) for rolling circle amplification (RCA) and the Nextera XT kit (Illumina, San Diego CA) with unique dual index sequences for library preparation (50). The protocol was modified to include two RCA reactions for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf tissue collection and propagation continued for a total of two rounds at each temperature following the above protocol. Frozen leaf tissue was ground, total DNA was extracted using the MagMax TM Plant DNA Isolation Kit (Thermo Fisher Scientific, Waltham, MA), and DNA < 6 Kb in size was selected using the Blue Pippin Prep system (Model # BDQ3010, Sage Science, Beverly MA) prior to library prep (50).…”
Section: Introductionmentioning
confidence: 99%